2021
DOI: 10.3390/ijerph18105119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultratrail Running on Neuromuscular Function, Muscle Damage and Hydration Status. Differences According to Training Level

Abstract: The status of trail running races has exponentially grown in recent years. The present study aimed to: (a) evaluate the acute response of ultratrail racing in terms of neuromuscular function, muscle damage and hydration status; (b) analyze if responses could differ according to training levels. Twenty runners participated in the present study. The participants were divided into amateur training level (n = 10; 43.30 ± 4.52 years) or high level competitors (n = 10; 41.40 ± 6.18). Neuromuscular response (squat ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 88 publications
2
17
0
1
Order By: Relevance
“…For the parameters of neuromuscular function, significant reductions in the height of the jumps have been reported in the scientific literature [ 7 , 21 , 27 , 44 ]. In this sense, both Martínez Navarro et al and Balducci et al reported decreases in flight height in the use of isolated tests of the Bosco jump protocol, both for SJ (pre = 24.4 ± 4.1 vs. post = 18.4 ± 42.2) [ 42 ] and for CMJ (pre = 30 ± 0.6 vs. post = 24 ± 0.5 cm) [ 43 ] respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For the parameters of neuromuscular function, significant reductions in the height of the jumps have been reported in the scientific literature [ 7 , 21 , 27 , 44 ]. In this sense, both Martínez Navarro et al and Balducci et al reported decreases in flight height in the use of isolated tests of the Bosco jump protocol, both for SJ (pre = 24.4 ± 4.1 vs. post = 18.4 ± 42.2) [ 42 ] and for CMJ (pre = 30 ± 0.6 vs. post = 24 ± 0.5 cm) [ 43 ] respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth mentioning a more recent study about induced muscle fatigue that also describes losses in SJ, ABA and CMJ in pre and post-race situations. [ 7 ]. In the present study, we found that the flight height of SJ, CMJ and ABA decreased in the post-race and also during the recovery period (see Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations